Strategi Berdagang Buah Kios di Pasar Pagi Arengka Kota Pekanbaru - Monica, Sherly (Jurnal Ilmiah Wahana Pendidikan, 2025)
The phenomenon of the informal sector, including traders, is a common and growing phenomenon, one of which is in Indonesia. The increase in the informal sector is caused by the limitations of the formal sector in accepting more workers. One of the jobs in the informal sector is fruit traders. In business, fruit traders cannot be separated from what is called the existence of strategy, so that the growing role of strategy in the fruit trader community can contribute to supporting smooth activities in fruit traders. The aim of this research is to find out what strategies fruit traders use in selling fruit at the Arengka Morning Market, Pekanbaru city. In the midst of many traders selling fruit. This research was conducted with a descriptive qualitative approach using purposive sampling techniques. In this study, the researcher took 5 informants as subjects in research related to the formulation studied by the researcher. Through interviews, documentation and observation, researchers succeeded in finding and obtaining data regarding the profile of fruit traders, the obstacles and risks experienced by fruit traders, the reasons why fruit traders choose fruit as merchandise, as well as the forms of fruit traders' trading strategies used by traders at Pasar Pagi. Arengka, Pekanbaru city.